Lentes, memórias e história : os fotógrafos lambe-lambe em Aracaju 1950-1990 - Oliveira, Cândida Santos de (2020)
This research deals with the history of lick-lick photography in Sergipe territory, highlighting the challenges, the pratices of the photography professional in the period 1950-1990. The lick-lick photographer can be considered an important agent responsible for the democratization and popularization of the photographic portrait among the less privileged classes of our society. Lick-lick ceases to exist due to the emergence of new technologies, such as digital photographic cameras, which gained strength in the 1990 s. It is the historian’s role to collect and ensure that experiences that can provide the cultural enrichment of society are not lost. In this sense, the approach approach was structured on two fronts: the history of photography and its relationship with the technique and aesthetic dimension of lambe-lambe, places of business and social actors.